An astro-green criminological examination of orbital space debris - Lampkin, Jack 19XX- (Criminology & criminal justice, 2025)
The aims of this study were to (1) highlight the importance of orbital debris as an environmental and green criminological issue, (2) build on recent work in astro-green criminology and (3) analyse orbital debris from an astro-green perspective with a focus on social and ecological harms consistent with green-critical criminologies. Human-made active and defunct debris continues to accumulate in Earth orbit littering near-Earth orbital space. There are a small number of key drivers, including accidental collisions between objects, in-orbit explosions and anti-satellite missile testing. Such activities pollute Earth orbit causing problems for astronomy, space travel and human and non-human populations on Earth. This is a theoretical, literature-based analysis of orbital debris from an astro-green criminological perspective. Criminology has had little to say about space debris because its creation is not a criminal offence. This article makes a unique contribution to criminological literature by applying the emerging perspective of astro-green criminology to orbital debris.